EVALUATION OF RISK FACTORS FOR INTRAHEPATIC CHOLESTASIS OF PREGNANCY IN PATIENTS PRESENTING TO A TERTIARY CARE CENTRE: Intrahepatic Cholestasis of Pregnancy - Anwar, Rabiah; Razzaq, Kashif; Shahid, Aysha; Afsheen, Afeera; Tariq, Amera; Saleem, Irum (Pakistan Armed Forces Medical Journal, 2021)
Objectives: To evaluate the principal risk factors associated with development of intrahepatic cholestasis of pregnancy (ICP) in patients presenting to a tertiary care hospital.Study Design: Case control study.Place and Duration of Study: Department of Gynaecology and Obstetrics, Pakistan Naval Ship Shifa Hospital Karachi, from Jan to Dec 2019.Methodology: All pregnant women with symptoms of intrahepatic cholestasis of pregnancy confirmed on history, examination and investigations were included. A comparison cohort of pregnant women with neither hepatobiliary nor medical illness associated with pregnancy was selected. Comparison of risk factors was done between both the groups.Results: Out of 6932 obstetric patients, 90 (1.29%) had intrahepatic cholestasis of pregnancy. Pruritis was cardinal symptoms in all (100%) the patients followed by excoriation marks (75.55%). Intrahepatic cholestasis of pregnancy was significantly found in women with multiple pregnancy (OR=1.81; 95% CI 0.51-6.42), antecedent intrahepatic cholestasis of pregnancy (OR=36.81; 95% CI 8.53-158.79), family history of intrahepatic cholestasis of pregnancy (OR=17.80; 95% CI 2.29-137.91) and history of pruritis with obstetric cholestasis of pregnancy use (OR=16.25; 95% CI 0.91-289.08).Conclusion: Intrahepatic cholestasis of pregnancy was observed in less than two percent cases. Risk of intrahepatic cholestasis of pregnancy was found to be increased with multiple pregnancies, antecedent intrahepatic cholestasis of pregnancy, family history of intrahepatic cholestasis of pregnancy and history of pruritis with prior obstetric cholestasis of pregnancy use.